2022
DOI: 10.1128/aem.00530-22
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Drought, but Not Short-Term Warming, Alters the Gut Microbiomes of Wild Anolis Lizards

Abstract: As climate change progresses, it is crucial to understand how animals will respond to shifts in their local environments. One component of this response involves changes in the microbial communities living in and on host organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 91 publications
3
7
0
Order By: Relevance
“…For example, in Pellerin et al [16], the impact of warming on life-history traits varied across years and could be explained by inter-annual variation in climate treatments or/and by lizards adaptation/acclimation to warming [49]. Our results further suggest that the climate effects become stronger in the long term, consistent with another study that showed that the gut microbiome of the slender anole is resilient to warming in the short term but affected in the long term [50]. Both observations highlight that climate effects may progressively settle in time and emphasize the importance of long-term experiments when studying the response of the gut microbiome under climate change.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in Pellerin et al [16], the impact of warming on life-history traits varied across years and could be explained by inter-annual variation in climate treatments or/and by lizards adaptation/acclimation to warming [49]. Our results further suggest that the climate effects become stronger in the long term, consistent with another study that showed that the gut microbiome of the slender anole is resilient to warming in the short term but affected in the long term [50]. Both observations highlight that climate effects may progressively settle in time and emphasize the importance of long-term experiments when studying the response of the gut microbiome under climate change.…”
Section: Discussionsupporting
confidence: 88%
“…This study provides the first evidence that climate change is altering gut microbiotas in a longitudinally monitored wildlife population. These findings are in line with cross-sectional studies that have also found support for climate-induced changes to gut microbiotas in wild polar bears and anoles (Watson et al, 2019;Williams et al, 2022), and experimental studies that demonstrate the direct link between temperature and the gut microbiota across taxonomically diverse hosts (Chevalier et al, 2015;Li et al, 2023;. A major goal for future research is to identify the proximate mechanisms underpinning the link between climate change and changes in gut microbiotas.…”
Section: Discussionsupporting
confidence: 84%
“…However, little is known about how climate change and pathogen dynamics interact to shape the gut microbiota, a diverse bacterial community that is crucial for host physiological homoeostasis, pathogen defence, and thermal tolerance (Alavi et al, 2020; Honda & Littman, 2016; Jaramillo & Castañeda, 2021). Recent evidence suggests that the gut microbiota is affected directly and indirectly by climate change (Greenspan et al, 2020; Sepulveda & Moeller, 2020; Watson et al, 2019; Williams et al, 2022). However, whether such responses are adaptive or maladaptive for animal hosts remains unclear, because longitudinal time‐series data that document gut microbial responses to climate change in natural populations, and the consequences for host fitness, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome-mediated plasticity may assist animals in acclimatizing or adapting to environmental change (11,12). Since microbiomes are highly dynamic, they can change on a more rapid timescale than their animal hosts in response to environmental pressures (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome-mediated plasticity may assist animals in acclimatizing or adapting to environmental change (11, 12). Since microbiomes are highly dynamic, they can change on a more rapid timescale than their animal hosts in response to environmental pressures (1219). Gut microbiota, in particular, play many vital roles in host physiology (2023), and environmental change may lead to an imbalance in the microbiome, which can have negative outcomes for hosts.…”
Section: Introductionmentioning
confidence: 99%